2020
DOI: 10.2174/1385272824666200219091830
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Strategies and Biological Potential of Coumarin-Chalcone Hybrids: A New Dimension to Drug Design

Abstract: Privileged scaffolds are ubiquitous as effective templates in drug discovery regime. Natural and synthetically derived hybrid molecules are one such attractive scaffold for therapeutic agent development due to their dual or multiple modes of action, minimum or no side effects, favourable pharmacokinetics and other advantages. Coumarins and chalcone are two important classes of natural products affording diverse pharmacological activities which make them ideal templates for building coumarin-chalcone hybrids as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 167 publications
2
5
0
Order By: Relevance
“…These results could be explained by the fact that both, coumarin and chalcone, involve many anticancer mechanisms, including cell cycle arrest, ROS production and apoptosis [31,58–60] . This is also in accordance with those previous reports made by Wang and colleagues [46] who showed a coumarin‐chalcone hybrid which efficiently delivered to cells to induce apoptosis through the generation of intracellular ROS in a colorectal carcinoma cell line HCT116.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results could be explained by the fact that both, coumarin and chalcone, involve many anticancer mechanisms, including cell cycle arrest, ROS production and apoptosis [31,58–60] . This is also in accordance with those previous reports made by Wang and colleagues [46] who showed a coumarin‐chalcone hybrid which efficiently delivered to cells to induce apoptosis through the generation of intracellular ROS in a colorectal carcinoma cell line HCT116.…”
Section: Resultssupporting
confidence: 89%
“…These results could be explained by the fact that both, coumarin and chalcone, involve many anticancer mechanisms, including cell cycle arrest, ROS production and apoptosis. [31,[58][59][60] This is also in accordance with those previous reports made by Wang and colleagues [46] who showed a coumarin-chalcone hybrid which efficiently delivered to cells to induce apoptosis through the generation of intracellular ROS in a colorectal carcinoma cell line HCT116. Besides, in other study, Singh and colleagues [61] had demonstrated that a coumarin-chalcone hybrid caused cell cycle arrest at G2/M phase and induced intrinsic caspase-dependent apoptosis mediated by alterations in the cellular levels of Bcl-2 family proteins in cervical cancer cell lines (HeLa and C33A).…”
Section: Antiproliferative Effect Of Hybrid 3c On Human Colorectal Ad...supporting
confidence: 91%
“…The free radical scavenging activity of Mn 3 O 4 was investigated by ABTS and DPPH methods. , In brief, taking the volume ratio of 1:1 for ABTS reserve solution (7 mM) and K 2 S 2 O 8 solution (2 mM), they were mixed and then put in a refrigerator of 4 °C for 12 h in the dark to generate ABTS radicals, which were diluted 50 times with absolute ethanol before use. Different concentrations of Mn 3 O 4 were taken as 0, 0.02, 0.04, 0.06, 0.08, and 0.10 mg/mL and added to the mixture separately.…”
Section: Methodsmentioning
confidence: 99%
“…5. forefront since it presents a selective, sensitive, and accurate determination of chalcone diastereomers to contribute to the progress of chalcone-based drug discovery [16][17][18][19][20]. The optimized method was fully validated as per the ICH guidelines.…”
Section: Methods Validationmentioning
confidence: 99%